MEMBANGUN KETERAMPILAN BERBICARA SISWA SD MELALUI DISKUSI SASTRA DI KELAS 3 SD NEGERI 5 LANGSA - Gaol, Yani M Lumban; Helsandy, Nazwa Alayda; Ulfah, Salwa; Putri, Febrina; Ariefriqasyi, Teuku M; Juliati (Universitas Negeri Medan, 2025)
The purpose of this study was to implement literature discussion in grade 3 of SDN 5 Langsa to improve elementary school students’ speaking skills. Speaking skills are an important component of language acquisition that helps students communicate well. According to previous studies, discussions, especially literature discussions, can improve speaking courage, vocabulary, and sentence structure. In this situation, literature discussion not only introduces students to age-appropriate children’s literature but also encourages them to actively participate in discussions, understand what they read, and express their own opinions. This method strengthens the affective aspect in language learning while creating a fun and meaningful learning atmosphere. Students are encouraged to speak more focused and confidently by combining reading, understanding, and discussing stories. The results of this study indicate that literature discussion can be a useful method to improve elementary school students’ speaking skills more contextually and naturally.